Spirit of India : Reflecting the Concerns, Aspirations and Dreams of the Indian Youth - A.P.J. Abdul Kalam (Rajpal & Sons, 2016)
Spirit Of India, by A P J Abdul Kalam, is a book focused towards the connection of youth and nation. This book revolves around the aspirations, issues, and dreams of the Indian youth in the contemporary India. As the time has changed over sixty decades of independence, the population of the youth has grown to require more and more education, growth in career, and overall development. In this time of personal ambitions, the spirit of one-India looks endangered to the author as has been addressed in this book.There has been an increase in unhealthy politics, economic differences, and national boundaries creating disturbances, which has questions the idea of nationhood. The author shows serious concerns for every individual s growth while also looking at the overall development of the nation.The book has intellectual discussions on a serious topic of national sentiments. Kalam has woven this subject into an inspiring book that lets the readers connect to the content. The book provides food for thought to the Indian youth, and guides them by simplifying their concerns and viewpoints.Kalam also presents his belief that unless each individual succeeds, the nation cannot achieve success. The statements are interlaced with reasoning and example to make the readers think. The progress of every individual depends upon securing the feeling of nationalism and not forgetting the core values. The first edition of Spirit Of India was published by Rajpal And Sons in 2013. It is available in paperback.